Local Wisdom of Making Alcohol in Natural Science Learning in Elementary Schools - Diah Utami, Ratnasari; Minsih; Sari Sitepu, Melyani; Hasyda, Suryadin; Aiman, Ummu; Puji Rahmawati, Fitri; Maftuhah Hidayati, Yulia; Desstya, Anatri; Tadzkiroh, Ummi; Azzahro Hazima, Atika; Fitri Rahmawati, Anisa (Universitas Pendidikan Ganesha, 2023)
The 2013 curriculum is oriented towards producing quality students who are rooted in the nation's culture and are developed based on a global perspective. The process of making alcoholic beverages, is one example of integration elements of natural science and local wisdom as a form of cultural preservation. However the school still have lack of references and sensitivity to efforts to explore the local wisdom activities of the community, especially in the alcohol-making process. This research aims to analyse the ethno science study on the alcohol-making process in natural science learning in elementary schools. This study used a qualitative approach and is included in the ethno science research type. The data source in this study was determined through a purposive sampling technique, with two alcohol makers as the subjects. These research’s objects consisted of the alcohol-making process and ethnoscience studies in alcohol making process in natural science learning in elementary schools, which were obtained through interviews, observations, and documentation. The analysis technique employed was the Miles and Huberman model (data reduction, presentation, and verification). The results uncovered that the alcohol-making process it is associated with natural science learning materials in elementary schools, it relates to phase transition, convection (heat transfer), conductors, and energy sources.